Drivers of Green Supply Chain Initiatives on the Economic Performance of SMEs In Malang - Surachman, Surachman; Aisjah, Siti; Prabandari, Sri Palupi (University of Merdeka Malang, 2024)
Green Supply Chain Management (GSCM) is a strategic concept of sustainable enterprise development that emerged from the